Survival Strategies and Online Marketing in the Time of the COVID-19 Pandemic of Bandung City SME: A Case Study of the Cibaduyut Shoe Center - Dindin Abdurohim; Andry Mochammad Ramdan (Quantitative Economics and Management Studies, 2022)
This study aims to describe and analyze survival strategies and online marketing strategies for small shoe businesses during the COVID-19 pandemic in Bandung. This study uses a qualitative method with a case study approach. Data were obtained by interviewing knitting business actors and related parties as key informants. The results showed that the COVID-19 pandemic had a negative impact on small shoe businesses in the shoe center of Bandung city. As a strategic step in the midst of a pandemic, business people use a survival strategy, by not increasing selling prices, but reducing profit targets, in the online marketing strategy of knitting small businesses using strategies: e-commerce, digital marketing, improving product and service quality, and customer relations. The implementation of this strategy is driven by an entrepreneurial spirit, flexibility, responsiveness to changes and technological developments, and the ability to collaborate with various stakeholders. This research shows that small businesses that implement survival strategies and online marketing are able to survive and improve business performance.